(3QjGOI GdCYeGd (B((3GdebGhdGJjI(B) :s (3ef GdacQI Edi GdJLSjO (B/s - (3adGb, eMeOs ((3GdLRGFQ(B: s (3CdaG ddhKGFb(B, s, 2022)
(3CSGSjGJ GdebGhdGJjI, UaGJ hegGQGJ GdebGhd,GdEHOGY hGdGHJcGQ heMaRGJg, CSHGH fLGM haTd GdebGhdGJ, eY GdehGba GdebGhdGJjI GdeNJdaI, cPdc NWhGJ GfTGA GdebGhdI heNWW GdCYeGd hGdCLgRI GdeNJUI aj GdeQGabI eY BdjGJ JTLjY GdebGhdGJjI aj GdLRGFQ(B: (3OGQ GdebGhdGJjI CfehPLGs
(3eQGLY U(B.219s
Keywords: (3GdebGhdGJs